Numeracy: How About Student of Junior High School Ability to Solve Problem Use Conten Uncertainty and Data with Personal Contex? - Tsaqifah, Sofi; Sujadi, Imam; Pramudya, Ikrar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2024)
Numeracy is part of the Minimum Competency Assessment (MCA) which is defined as the ability to think using mathematical concepts, procedures, facts, and tools to solve everyday problems in various relevant contexts. The assessment components in numeracy include content, context, and cognitive processes. Content in numeracy includes coverage of algebra, numbers, geometry and measurement, and data and uncertainty. Components in the cognitive process include three aspects understanding, application, and reasoning. The context of numeracy is related to personal, socio-cultural, and scientific. This research uses data and uncertainty content with a personal context. The research conducted is qualitative research with data collection using task-based interviews conducted twice with one question for each test conducted. Subjects were selected based on student mastery of data and uncertainty material and the subjects selected were students who had good communication. Data collection was carried out by giving written tests and followed by interviews. The results of the task-based interview were then analyzed and conclusions were drawn. The results obtained are the ability of students to solve numeracy problems on data content and uncertainty with personal contexts including the application cognitive process. The indicators of ability mastered by students include: students are able to master indicators of mathematical facts, students are able to master indicators of mathematical concepts, and students are able to master indicators of mathematical tools.